2022
DOI: 10.2174/1871520621666210903120253
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Nerium oleander Distillate and Tarantula cubensis Alcoholic Extract on Cancer Biomarkers in Colon and Liver Tissues of Rats with Experimental Colon Cancer

Abstract: Background: Colon cancers are among the three major cancer types that result in death. The research for effective treatment continues. Objective: The aim of this study is to determine the effects of Tarantula cubensis alcoholic extract (TCAE) and Nerium oleander (NO) distillate on the levels of midkine, TGF-β, VEGF, AFP, COX-2, IGF and caspase 3 in liver and colon tissues of experimentally induced colon cancer in rats. Method: The liver and colon tissues of the rats were divided into Control, Colon Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Er et al [18] found that TCAE administration in rats with CRC decreased the number of ACFs and increased levels of PGE-2, IL-2, and IL-10. TCAE is reported to suppress increases in midkine, TGF-β, VEGF, AFP, COX-2, IGF, and Cas-3 levels in the colon [41]. It has been reported that Flavanol can change Bax and Bcl-2 expression levels at different rates in different cell lines [42].…”
Section: Crc + Tcae Crc + Capecitabine Crc + Tcae + Capecitabinementioning
confidence: 99%
“…Er et al [18] found that TCAE administration in rats with CRC decreased the number of ACFs and increased levels of PGE-2, IL-2, and IL-10. TCAE is reported to suppress increases in midkine, TGF-β, VEGF, AFP, COX-2, IGF, and Cas-3 levels in the colon [41]. It has been reported that Flavanol can change Bax and Bcl-2 expression levels at different rates in different cell lines [42].…”
Section: Crc + Tcae Crc + Capecitabine Crc + Tcae + Capecitabinementioning
confidence: 99%